2017
DOI: 10.3126/ajms.v8i1.15878
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between maxillary sinus floor topography and relative root position of posterior teeth using Orthopantomograph and Digital Volumetric Tomography

Abstract: Background: Maxillary sinus and its close proximity to the oral cavity make it a common clinical concern for medical and dental practitioners. Due to anatomical complexities, it is difficult to evaluate the relation between the root apices of maxillary posterior teeth and the floor of maxillary sinus which is essential for diagnosis of sinus pathology, understanding the path of dental infection and planning of dental treatment. Aims and Objectives: To correlate the topographic relationship of the maxillary sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
3
5
0
7
Order By: Relevance
“…An OPG is usually sufficient in detecting when root tips are a distinct distance from the sinus. Lopes et al found 78% agreeance between both modalities when the root tip was a distinct distance from the sinus, and Kalkur et al found 85% agreeance in the same situation . Hassan found 56.1% correlation, and while this value is lower than the other studies, it represented the highest correlation between CBCT and OPG in this study.…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…An OPG is usually sufficient in detecting when root tips are a distinct distance from the sinus. Lopes et al found 78% agreeance between both modalities when the root tip was a distinct distance from the sinus, and Kalkur et al found 85% agreeance in the same situation . Hassan found 56.1% correlation, and while this value is lower than the other studies, it represented the highest correlation between CBCT and OPG in this study.…”
Section: Discussionsupporting
confidence: 43%
“…Hassan found 56.1% correlation, and while this value is lower than the other studies, it represented the highest correlation between CBCT and OPG in this study. These results showed that OPG is accurate in assessing this relationship. Evidently, when the OPG shows a distinct distance between the roots and the sinus, it is unnecessary to order a CBCT.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations